Evaluation of different impression techniques for indirect e-max fixed dental prostheses. Randomized clinical trial - Sara Linga; Saba Lanqa; Daniah Basheer; Majed Alahmari; Salah A. Yousif (Elsevier, 2019)
Introduction: Nowadays, it is a new era in prosthetic dentistry, due to the use of digital impressions and new digital computer-aided methods for designing and manufacturing computer-aided design/computer-aided manufacturing (CAD/CAM). Now, we are trying to change all the old traditional methods to have better results. Some studies found that there is no significance between the overall survivals of the tooth supported and implant CAD CAM fabricated prostheses. In addition, there is no difference in accuracy. Making single crowns or short span bridges can be done efficiently with digital impressions. In addition, it was found that digital impressions could be more reproducible. Materials and methods: This randomized clinical study evaluated three impression techniques. Ten participants demanding three units all-ceramic bridges were involved in the study. The inclusion criteria were from 18 to 60 years group age; the patient should have plaque score and bleeding score <25%, with good periodontal state, with one missing tooth in need to three units fixed dental prosthesis, with sound or properly restored neighboring and opposing teeth. Sequencing of the different impression techniques investigate is determined according to computer-generated randomization list. The sequence of the different impression techniques was concealed by sealed envelopes until the date of the participant clinical visit. Three operators (R.A, M.M, and R.G.) Performed the impressions. Results: Almost 50% of the participants were male and the rest were female, with mean age 37.3 from range (from 20 to 50). Impressions were made to abutments of three units bridges. The mean of the procedure time ± SD was 336 ± 9.4 s for closed mouth technique impressions, 557 ± 8.2 s for the single-step traditional metal tray technique, and 397 ± 8.6 s for the Omnicam [Table 1]. Conclusions: It was found in our research that the closed mouth technique is the fastest, with best patient acceptance and best operator easiness evaluation followed by the digital procedures, which are preferred over the conventional trays as approved by the previous studies in the literature.